Die Lebenszeugnisse Oswalds von Wolkenstein, Band 5 Band 5: 1443-1447, Nr. 387-524, Edition und Kommentar - Schwob, Anton (2013)
Until today, the death of Charles VI and Maria Theresia's ascending the throne 1740 is seen as a major turning point in Austrian history. But now is the question of whether in different "layers" and "rooms" without doubt fundamental change between 1720 and 1780 not differentiated must be seen against the background of the concept of interface ("Sattelzeit"/Reinhart Koselleck). On the basis of the space "Viennese court", where the change of rulers in its effects most likely can be documented, attempts from the perspective of different disciplines (the so called "Hofkünste" - literature/poetry, arts, theatre/dance, music) point out continuities and discontinuities.